Navigating Diagnostic Challenges: A Case of Best Vitelliform Macular Dystrophy Misdiagnosed as Central Serous Chorioretinopathy - Amit Nandan Tripathi; Vipin Rana; Sandeepan Bandopadhyay; Pradeep Kumar (Delhi Journal of Ophthalmology)
This case report delineates diagnostic challenges in distinguishing best vitelliform macular dystrophy (BVMD) from central serous chorioretinopathy (CSC) in a 32-year-old male misdiagnosed initially with chronic CSC but later confirmed with BVMD. BVMD’s clinical resemblance to CSC, especially during its atrophic stage, complicates differentiation. Essential diagnostic tools including optical coherence tomography, fundus autofluorescence, electrooculogram, and genetic testing were crucial for accurate identification. Recognition of unique features such as autofluorescence and choroidal thickness variations aids in precise differentiation. Emphasizing precision in diagnosis, genetic counseling, and continuous monitoring highlights the imperative need to discern BVMD’s atrophic stage from CSC.